Nonstructural heart disease in the newborn. Observations during one year in a perinatal service. Issue 9 (September 1978) - Rowe, R D; Izukawa, T; Mulholland, H C; Bloom, K R; Cook, D H; Swyer, P R
Abstract : One-third of 327 newborn infants referred to the perinatal service of the Hospital for Sick Children during 1975 with suspected cardiopulmonary disorders proved to have nonstructural heart disease. Most of these were term infants with transient tachypnoea or cyanosis who recovered. A history of fetal distress or difficult delivery was commonly associated. The haemodynamic disorder for most was a delay in the normal progress of the transitional circulation. Evidence of myocardial ischaemia was present in 40%, and about half of these developed congestive heart failure. Aids to diagnosis of the ischaemic complication included echocardiography and myocardial perfusion scanning. For a small proportion specific metabolic disturbances, myocarditis, or dysrhythmia seemed the primary cause but even for these there were reasonable grounds to suspect a prenatal origin. Current general supportive measures were of value in treatment.